Adsorption of uranium from groundwater using heated aluminum oxide particles. (April 2021) - Lee, Gichang; Lee, Wontae
Graphical abstract: Highlights: HAOPs can efficiently adsorb uranium (VI) from groundwater in seconds. U(VI) adsorption increases at lower pH and lower temperature. Competitive anions exhibited adverse effect on U(VI) adsorption under circumneutral concentrations. U(VI) adsorption process is thermodynamically exothermic and spontaneous. Abstract: The adsorption of uranium, U(VI) from groundwater was investigated using heated aluminum oxide particles (HAOPs) which were manufactured from aluminum sulfate. The effects of adsorbent dosage, pH, water temperature, contact time, and initial uranium concentrations on the removal of U(VI) were assessed in batch tests using groundwater containing CaUO2 (CO3 )3 2− and Ca2 UO2 (CO3 )3 (aq) as dominant species. The maximum adsorption density ( q max ) value at pH 6.0 was relatively higher than those at higher pH because HAOPs with a negative surface charge readily bind with the cationic complexes (UO2 (OH) + and (UO2 )3 (OH)5 + ). U(VI) adsorption by HAOPs was higher at lower temperatures while the difference between 5 and 20 °C was not significant. The equilibrium adsorption capacity ( qe ) increased proportionally with increasing initial U(VI) concentration per specific amount of adsorbent. Anions such as sulfate and bicarbonate interfered with U(VI) adsorption at > 20 mM concentration. However, the U(VI) adsorption efficiency was not significantly changed by water temperature, pH and competing substances within the rages typically occurring in natural groundwater. The U(VI) adsorption by HAOPs rapidly reached saturation within 15 s, and was exothermic and spontaneous with chemical adsorption onto a single HAOP layer.